2017
DOI: 10.1002/jmor.20735
|View full text |Cite
|
Sign up to set email alerts
|

The colonic groove of the plains viscacha (Lagostomus maximus): Histochemical evidence of an abrupt change in the glycosylation pattern of goblet cells

Abstract: The ascending colon of most rodent species shows a longitudinal colonic groove that works as a retrograde transport pathway for a mixture of bacteria and mucus toward the cecum. We describe the morphology and glycosylation pattern of the colonic groove of Lagostomus maximus to analyze the role of mucins in this anatomical feature. We also studied the distribution pattern of the interstitial cells of Cajal (ICC) to evaluate their regulatory influence on gut motility. The groove originated near the cecocolic jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The α‐amylase‐PAS, K(OH)/PA*/Bh/PAS and PA/Bh/KOH/PAS techniques were used to study the presence of sugars, usually in organs that produce different types of mucins, since they allow differentiating certain features of a specific portion of carbohydrates (Lev & Spicer, ; McManus, ; Pearse, ; Reid, Culling, & Dunn, ; Volz, Reid, Park, Owen, & Dunn, ). In L. maximus, these techniques were applied to organs of the digestive system (Tano de la Hoz et al, ; Tano de la Hoz, Flamini, Zanuzzi, & Díaz, ). So far, there have been no studies referred to the ZP of the ovary of mammals using these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The α‐amylase‐PAS, K(OH)/PA*/Bh/PAS and PA/Bh/KOH/PAS techniques were used to study the presence of sugars, usually in organs that produce different types of mucins, since they allow differentiating certain features of a specific portion of carbohydrates (Lev & Spicer, ; McManus, ; Pearse, ; Reid, Culling, & Dunn, ; Volz, Reid, Park, Owen, & Dunn, ). In L. maximus, these techniques were applied to organs of the digestive system (Tano de la Hoz et al, ; Tano de la Hoz, Flamini, Zanuzzi, & Díaz, ). So far, there have been no studies referred to the ZP of the ovary of mammals using these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse studies have demonstrated that the rodent L. maximus is exclusively herbivorous and feeds on a great variety of plant species, such as annual and perennial herbs and small shrubs (Giuletti & Jackson, 1986; Jofre, 1994), showing preference for grasses (Bontti, Boo, Lindstrom, & Elia, 1999) and dicotyledons (Kufner & Monge, 1998). As part of its digestive strategy, it practices coprophagia, ingesting at least certain fraction of its own faeces, rich in proteins, minerals and vitamins, although poor in fibres (Clauss et al., 2007; Tano de la Hoz et al., 2017). This strategy is important to its absorptive activity, as it happens in other hystricomorphs (de Barros Moraes et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The results were evaluated by four independent observers using a semi‐quantitative scale to determinate the intensity of the reactions (0, negative; 1, weak; 2, moderate; 3, strong). These scores were established according to previous histochemical studies (Tano de la Hoz et al., 2014, 2017; Tano de la Hoz, Flamini, Portiansky, & Díaz, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensities of the different lectins were classified according to the following semi‐quantitative scale: 0, unlabelled; 1, light stain; 2, moderate stain; and 3, intense stain, according to the criterion used in previous studies (Acuña et al ., 2018; Tano de la Hoz et al ., 2016, 2017). The evaluation of the intensity of each reaction was based on estimates from three trained independent researches, blinded to the samples being observed.…”
Section: Methodsmentioning
confidence: 99%